Managing large capital inflows: Taking stock of international experiences - Susan Schadler (Asian Development Bank Institute (ADBI), 2008)
Two waves of large capital inflows to emerging markets in the past 20 years appear to present a paradox: inflows can provide opportunities for faster growth and technology transfer, but they can also feed overheating pressures and unleash forces that push recipients into crisis. This paper examines over 90 episodes of large inflows asking whether ill-effects were common or severe, how they were or were not avoided, and what circumstances resulted in the most successful episodes. The findings point to the crucial role of counter-cyclical fiscal policy during inflow episodes. Other protective steps-particularly in the area of financial sector supervision and development-can be equally important.
Keywords: E44; F36; F41; 330; Kapitalimport; Aufstrebende Märkte